2015
DOI: 10.1039/c4ta06643j
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin oxide shell coating of metal nanoparticles using ionic liquid/metal sputtering

Abstract: The indium sputter deposition into ionic liquids containing noble metal nanoparticles produces core–shell-structured metal@In2O3 with high thermal and electrochemical stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 54 publications
0
34
0
Order By: Relevance
“…The unique features of an IL, such as a negligible vapor pressure, wide electrochemical window, good thermal stability, antistatic properties, have led to many proposed applications thus far. Recently, we reported Pt‐nanoparticle‐supported carbon electrocatalysts easily produced by agitating Pt‐nanoparticle‐monodispersed ILs, which were prepared by magnetron sputtering onto the ILs, with various carbon supports, e.g., carbon nanotubes and carbon black, under heating conditions . The resulting electrocatalysts showed favorable catalytic activities for ORR and high durabilities .…”
Section: Summary Of the Pt‐nanoparticle‐supported Carbon Catalysts Usmentioning
confidence: 99%
“…The unique features of an IL, such as a negligible vapor pressure, wide electrochemical window, good thermal stability, antistatic properties, have led to many proposed applications thus far. Recently, we reported Pt‐nanoparticle‐supported carbon electrocatalysts easily produced by agitating Pt‐nanoparticle‐monodispersed ILs, which were prepared by magnetron sputtering onto the ILs, with various carbon supports, e.g., carbon nanotubes and carbon black, under heating conditions . The resulting electrocatalysts showed favorable catalytic activities for ORR and high durabilities .…”
Section: Summary Of the Pt‐nanoparticle‐supported Carbon Catalysts Usmentioning
confidence: 99%
“…X-ray photoelectron spectroscopy (XPS) 33 and a transmission electron microscope (TEM) equipped with energy dispersive spectroscopy (EDS) were also used to confirm the oxidization of boron and identify oxide shells 34 on the boron surface. The formation of surface oxide is supposed to decrease the potential energy (explosive energy) of the system and disturb the propagation of combustion 10 .…”
Section: Introductionmentioning
confidence: 99%
“…One thing to take into consideration though is that it is difficult to support Pt nanoparticles onto these carbon materials without breaking down the sp 2 structure due to their surface inertness. 23 We recently found that various metal nanoparticles, prepared by metal magnetron sputtering onto an ionic liquid (IL), 24,25 can be easily supported by carbon materials by heat treatment without the requirement of any further process, [26][27][28][29][30][31] e.g., glassy carbon (GC), highly oriented pyrolytic carbon (HOPG), and single-walled carbon nanotubes (SWCNTs), and thus concluded that the IL works as a glue to support the Pt nanoparticles onto these materials. 30 Very recently, Su et al proposed a similar idea, namely that a very thin IL layer could be formed on a nanocarbon material via an entrapping effect.…”
Section: Introductionmentioning
confidence: 99%